Peran Notaris Dalam Memberikan Penyuluhan Hukum Kepada Masyarakat Dan Tanggung Jawab Notaris Setelah Pensiun - Jufri Jufri (Jurnal Hukum Bisnis, 2023)
The aim of this research is to find out and examine the public's understanding of notarial deeds and their functions; the role of Notaries in providing legal understanding to the public in understanding the law and their responsibilities in making notarial deeds in Pohuwato Regency. The research method used is normative law using a statutory approach and a conceptual approach. The existence of an authentic deed as written evidence plays an important role in every legal relationship in people's lives, in various economic activities, activities in banking, land, social activities, etc. The need for written evidence in the form of authentic deeds is increasing in line with the growing demand for legal certainty in various economic and social relations, both at the national, regional and global levels. With an authentic deed, rights and obligations can be clearly determined, guaranteeing legal certainty and at the same time it is hoped that disputes can be avoided. As a public official, a notary is required to be responsible in carrying out his authority so that he can provide legal education to the public in accordance with the notary position law. The results of this research are (1) The role of Notaries in providing legal understanding to the public in understanding the law in relation to making notarial deeds is carried out by providing legal counseling to their clients, which can be divided into 2 (two) criteria, namely legal counseling followed by making the deed and legal counseling without being followed by making a deed. Legal counseling followed by making a deed is an inseparable unit; and (2) the notary's responsibility for authentic deeds made after the notary's position has ended or retired. This can be carried out by the authorized parties as long as the authentic deed has not been canceled by law within a period of 30 years from the date it was made by the Notary.